2014
DOI: 10.1186/cc13828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin therapy on mortality from infection and sepsis: a meta-analysis of randomized and observational studies

Abstract: IntroductionObservational data have suggested that statin therapy may reduce mortality in patients with infection and sepsis; however, results from randomized studies are contradictory and do not support the use of statins in this context. Here, we performed a meta-analysis to investigate the effects of statin therapy on mortality from infection and sepsis.MethodsWe searched electronic databases (PubMed and Embase) for articles published before November 2013. Randomized or observational studies reporting the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 55 publications
1
67
2
1
Order By: Relevance
“…The majority of clinical studies to date have been retrospective cohort studies evaluating the impact of prior treatment with statins on disease progression and mortality. Many of these, plus several meta-analysis reviews, showed promising results in which prior use of statins significantly reduced disease progression and/or mortality associated with sepsis (25,(28)(29)(30)(31)(32) Therefore, several studies have shown the promising potential of the prior use of statins in reducing the initiation or progression of infections. Nevertheless, it is difficult to draw conclusions on whether the effects of these statins were directly antibacterial/antiinflammatory or were due to pleitropic effects on comorbidities associated with the infections.…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of clinical studies to date have been retrospective cohort studies evaluating the impact of prior treatment with statins on disease progression and mortality. Many of these, plus several meta-analysis reviews, showed promising results in which prior use of statins significantly reduced disease progression and/or mortality associated with sepsis (25,(28)(29)(30)(31)(32) Therefore, several studies have shown the promising potential of the prior use of statins in reducing the initiation or progression of infections. Nevertheless, it is difficult to draw conclusions on whether the effects of these statins were directly antibacterial/antiinflammatory or were due to pleitropic effects on comorbidities associated with the infections.…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
“…A recent randomized control trial (RCT) investigating the effect of rosuvastatin on the clinical outcome of patients with sepsis-associated acute respiratory distress syndrome was discontinued because of futility (35). Moreover, a number of recent meta-analyses of RCTs suggested that there is no significant evidence to suggest that statin use improves the mortality outcome of patients with sepsis (25)(26)(27).…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
See 1 more Smart Citation
“…Initial observational studies showed promising results, and a meta-analysis of adjusted estimates from 26 observational studies (336,245 patients) showed a significant reduction in mortality with statin use [relative risk (RR) 0.65; 95 % CI 0.57, 0.75] [5]. However, randomized clinical trials (RCTs) failed to show mortality benefit with statins use.…”
Section: Statins and Mortality In Sepsismentioning
confidence: 99%
“…A recent meta-analysis [7] of observational studies which pooled the data from over 330,000 patients concluded that statin use in sepsis is associated with improved outcomes. This conclusion clearly comes with many caveats, mainly that association does not confirm causation and the multiple occasions introducing bias.…”
mentioning
confidence: 99%